Overview of the Past and Future G&G Activities in the Pattani Trough, Gulf of Thailand - Masashi Fujiwara (Science Faculty of Chiang Mai University, 2020)
Oil and gas exploration in the Pattani Trough, Gulf of Thailand was initiated in 1968 and since then more than 20 oil and gas fields have been discovered. As of the end of October, 2015 daily production was 1.7 BCF of gas, 140,000 barrel of condensate and oil, totally 430,000 barrels of oil equivalent. The Pattani Trough is a rift type-sedimentary basin of Cenozoic age and the maximum thickness of sediments is more than 10 km. Oil and gas are mainly trapped in fluvial to deltaic sandstones located between depths of 5,000 to 9,000 feet. Structure is characterized by many normal faults. ConocoPhillips and MOECO drilled the first exploratory well, Surat-1 in the Gulf of Thailand in 1971. The first successful exploratory well, 12-1 (Erawan-1), was drilled in 1972 by Union Oil (presently Chevron) and SEAPEC (presently MOECO). The first gas from the Erawan field was put on stream in 1981 and shortly after the commencement of production a shortfall issue occurred due to the smaller reserves per well than anticipated. This crisis was rescued through the reduction in the cost of drilling and facilities and the reduced geologic risk by using 3D seismic data to plan complex well paths to penetrate multiple gas reservoirs. The 3D seismic acquisition in the Erawan field was completed in 1980 only three years after the first 3D acquisition of the Bongkot field in the Gulf of Thailand. Since then more than 30 additional 3D seismic surveys have been carried out in the Chevron operated Blocks 10,11,12,13 totaling approximately 12,000 square kilometers. The most advanced interactive interpretation systems at the time, *SDS and *SIDIS were introduced in the early 1980s and although these were proto-type workstation they were used for both structural interpretation and for reservoir prediction. The first test for reservoir prediction was made by the Erawan E-4 well in 1982, however, it was unsuccessful. In general, it is understood that high amplitudes are directly related to the presence of sands but not necessarily the volume of gas and, in general, direct hydrocarbon prediction is not successful at this moment. This paper will briefly review the historical perspectives of seismic technology with some old-fashioned “legend” maps and the future exploration potential including the shallow hydrocarbon related to the Middle Miocene Unconformity (MMU) and Basement.